Alleviation of DSS-induced colitis in mice by a new-isolated Lactobacillus acidophilus C4 - Liu, Qianqian; Jian, Wenwen; Wang, Lu; Yang, Shenglin; Niu, Yutian; Xie, ShuaiJing; Hayer, Kim; Chen, Kun; Zhang, Yi; Guo, Yanan; Tu, Zeng (Frontiers in Microbiology, 2023)
Probiotic is adjuvant therapy for traditional drug treatment of ulcerative colitis (UC). In the present study, Lactobacillus acidophilus C4 (C4) with high acid and bile salt resistance has been isolated and screened, and the beneficial effect of C4 on Dextran Sulfate Sodium (DSS)-induced colitis in mice has been evaluated. Our data showed that oral administration of C4 remarkably alleviated colitis symptoms in mice and minimized colon tissue damage. To elucidate the underlying mechanism, we have investigated the levels of inflammatory cytokines and intestinal tight junction (TJ) related proteins (occludin and ZO-1) in colonic tissue, as well as the intestinal microbiota and short-chain fatty acids (SCFAs) in feces. Compared to the DSS group, the inflammatory cytokines IL-1β, IL-6, and TNF-α in C4 group were reduced, while the antioxidant enzymes superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) were found to be elevated. In addition, proteins linked to TJ were elevated in C4 group. Further study revealed that C4 reversed the decrease in intestinal microbiota diversity caused by colitis and promoted the levels of SCFAs. In conclusion, L. acidophilus C4 effectively alleviated DSS-induced colitis in mice by repairing the mucosal barrier and maintaining the intestinal microecological balance. Lactobacillus acidophilus C4 (C4) could be of great potential for colitis therapy.